Experiences focused on the improvement of the Continuity of Care Program of a Community Mental Health Center, 2018-2021 - Quispe Carmelo, Marco Antonio (2022)
Programs aimed at improving the mental health of users require records to improve the actions of the personnel who coordinate them. The purpose of the study was to systematize the experiences in the improvement of the Continuity of Care Program of the Community Mental Health Center La Victoria, Peru. The research was configured within a qualitative approach, with a participant action research design, complying with the phases of diagnosis, planning, execution, systematization and evaluation. Eight health professionals and five users with mental health problems participated. Information was obtained through focus group interviews and documentary review, where three categories emerged as a result of the triangulation of the information provided by the informants. The findings were that the experiences focused on the improvement of the Continuity of Care Program of the Mental Health Center allowed through the implementation of an activity plan to facilitate changes in the functional organizational structure of the program, the improvement of care based on the change of the approach based on the user's needs from a humanizing and interdisciplinary vision; in relation to the improvement of the continuity of care, the care was increased and responded to the diagnostic and clinical needs in a systematic way. In relation to the improvement of the criteria, defined specifications emerged taking into account the symptomatology of the users, the risk classification that facilitated the direction of the multidimensional evaluation and regulation of the interventions, which benefited the participants of the program.